The multiple synthesis of 2D layered Ti3C2Tx/Ag/MWCNTs/Ag composites with enhanced electrochemical properties. Issue 2 (15th January 2023) - Zhang, Yan; Guo, ZhiJin; Zhou, JianPing; Sun, DaQian; Li, HongMei
Abstract: MXene, a novel two-dimensional material composed of alternating transition metal carbon/nitrogen, has the advantages of large specific surface area, many active sites, and short ion transport paths, and has shown great potential in the field of capacitors in the beginning. However, the unique two-dimensional structure is prone to collapse and accumulation, which inhibits the electron migration rate and ion penetration, resulting in poor energy storage capacity. In this paper, Ti3 C2 Tx /Ag/MWCNTs/Ag composites with good capacitive properties were successfully prepared by Ti3 C2 Tx which directly reduces silver nitrate solution and further introduces nanoscale MWCNTs. Ag NPs are introduced twice to grow and distribute uniformly on the surface and between the layers of Ti3 C2 Tx to play a supporting role. The introduction of MWCNTs in the intermediate process can enter the interlayer and act as spacers together with Ag NPs to prevent the collapse and stacking of Ti3 C2 Tx and improve its surface utilization. However, the preparation process unavoidably leads to partial oxidation of Ti3 C2 Tx, which deteriorates its electrochemical properties. Owing to the synergy between Ti3 C2 Tx, Ag NPs and MWCNTs, the Ti3 C2 Tx /Ag/MWCNTs/Ag composites show good electrical conductivity, low internal resistance (0.67 Ω) and extreme high capacitance contribution (97%) in electrochemical tests.